Formation in Family and Educational Institutions of Orthodox Form of Thinking and Communication - Evgeny Bryndin (Journal of Advanced Research in Education, 2023)
Man is the interconnection of spirit, mind, soul and body. The body is the dwelling of the soul. The soul is the dwelling of the spirit, the source of life of the body, desires and feelings of man. The mind gives rise to thoughts and carries out their linguistic design. Thought is of a spiritual nature. The spirit penetrates into the living information of nature, into the soul and body, communicates with the spirits of other people. Jesus communicated with spirits. The human spirit communicates through prayer with God as a spiritual entity. He is the spiritual, moral, moral and ethical leader of the thinking, behavior and being of a person. Mind, spirit, soul and memory form a person in the process of human life. A person thinks and has spiritual qualities. Psalm 18:3 describes the nature of thinking. The night of the night reveals knowledge by penetrating the spirit into the living information of nature. Day to day conveys speech (communication) based on existing language knowledge. Communication can be live with people or with their knowledge. Communication with knowledge is carried out in the process of learning and creativity. Learning and creativity based on knowledge is carried out in the form of independent communication. In the process of communicating with people, a person manifests and forms the quality of the spirit. When communicating with righteous peaceful people, the spirit acquires useful qualities. When dealing with corrupt people, the spirit acquires pernicious qualities. The spirit of a child inherits generic qualities. In the process of communication, the spirit must learn to pacify the pernicious tribal qualities. The qualities of the spirit determine the ethical direction of thoughts and their linguistic design. In educational institutions, it is useful to study the spiritual laws of the Gospel, so that through their prism, children distinguish between good and evil and formed the right worldview, by reading literature and studying history, social sciences and cultural studies.